37 Enhance GP-Geriatrician Care Homes Multidisciplinary Team. (6th February 2020) - Ruiz-Mendoza, E; Penart, A; Obi, I; Addison, E; Clark, H
Abstract: Introduction: Peterborough Care Home Support Team (CHST) have worked on a small pilot of 4 care homes with a local GP and an interface geriatrician to address the complex needs of the residents within those care homes to improve patient experience, quality of care and reduce attendances and admissions to hospital in a geographical area of 5000 care home beds. Methods: The multidisciplinary team (MDT) consisted of a General Practitioner, Interface Geriatrician, Pharmacist from the medicine optimisation team and Care Home Support Team member with once a month meeting in the selected Care Home. We measure the impact of our intervention comparing the data predating our intervention comparing 4 selected care homes with high A&E attendances in each period 2017 and 2018. Results: 50% reduction in hospital attendances with £4985.48 cost saving following medication review in the 4 care homes under study. Conclusions: Commissioners, Local Authorities and Care Home Providers have started to look towards more innovative solutions to improve patient experience, quality of care and reduce attendances and admissions to hospital. Our experience and results aim to consider enhance GP-Geriatrician Care Homes MDT as a good model of care.